Predictors of severe exacerbations, poor asthma control, and β-agonist overuse for patients with asthma - Patel, Mitesh; Pilcher, Janine; Reddel, Helen K.; Qi, Victoria; Mackey, Bill; Tranquilino, Tyronne; Shaw, Dominick E.; Black, Peter (Elsevier, 2014)
Background: Predictors of asthma exacerbations, poor asthma control, or extreme β-agonist overuse may be of clinical utility in the management of asthma.